Nanostructured Al Doped SnO2 Films Grown onto ITO Substrate via Spray Pyrolysis Route - Benhaliliba, M.; Benouis, C. E.; Ocak, Y. S.; Yakuphanoğlu, Fahrettin (Sumy State Univ, Dept Marketing & Mia, 2012)
We report on nanostructured films of Al doped tin oxide grown by facile spray pyrolysis route, and their physical properties were investigated. The sprayed films were grown onto indium tin oxide (ITO) substrate at 300 degrees C from the precursor (SnCl4, 5H(2)O). The content of Al is kept at 3 % in the solution. Structural, optical, electrical and surface properties were investigated. X-rays pattern reveals polycrystalline structure and SnO2 phase occurence. The visible transmitance exceeds 85 %, the band gap is found to be 3.7 eV. Nanotips were observed by 3D atomic force microscope (AFM) observation. Using the Hall effect measurements system (HMS), the films exhibit very low resistivity found to be 9.85 10(-5) Omega.cm, a high electron concentration is around 10(21) cm(-3), and the mobility reaches the value of 20 cm(2)/Vs.
Keywords: Al doped tin oxide; Sprayed films; ITO substrate; Nanostructured films; Transmittance; Hall measurement